(3GdhUa aj GdbQBf GdcQje (B/s - (3LGSe, jhfSs; (3GdUGdM, UHMjs 1926-1986; (3GdRMjdj, hgHI eUWais 1932-2015 ((3OeTb (B- (3ShQjG (B:s (3OGQ GdecJHj ddWHGYI hGdfTQ,s, 1995)
(3gPG GdcJGH gh UhQI HjGfjI MjI dChUGa GdbQBf hUhQg GdeDKQI aj GdEfSGf GdPj gh eMhQ GdNWGH GdEdgj, ShGA cGf eDefG Ce cGaQG hjMedg Ydi GdEjeGf hGdEPYGf hGdEbQGQ HUOb GdbQBf, hGdJUOjb HGdfHhGJ hGdhMj GdEdgj, hNJeg HfHhI NGJe GdCfHjGA(B. (3ceG Ted GdcJGH hUa GdLfI hGdfGQ hjhe GdbjGeI hhUa GdHYK hGdMSGH, hhUa hbGFY GdOghQ heG MhJg ef eTGgO GdNQGH hGdOeGQ ddCbhGe GdeYPHjf(B.s
(3CUdG CWQhMI (B((3eGLSJjQ(B)-(3LGeYI OeTb, (B[1984]s
Keywords: (3bQBfs -- (3eHGMK YGeIs